Non-Standard Employment and Wage Differences across Gender: a quantile regression approach - Anil Duman (Global Labor Organization (GLO), 2020)
The paper aims to identify the effect of non-standard employment on wages in the Turkish labour market across gender and decompose the gap to understand the role of endowments and returns in generating the earning differences. Our findings show that non-standard employment reduces wages for women at every quantile but no such results are attained for men. Besides, females with standard jobs in Turkey earn more than men, however, the opposite holds for females in non-standard positions. Also, a big part of the gender pay gap is attributable to returns, especially at the lower end of the distribution. Women in low-paid and atypical jobs face larger pay gaps, and the role of unexplained component suggests they are discriminated. The distinct impact of non-standard employment on men and women suggest that policies geared towards labour market flexibilisation should take gender perspective into account.
Keywords: J31; J24; J41; 330; Non-standard employment; Gender pay gap; Quantile regressions; Recentered Influence Function (RIF); Decomposition; Discrimination